Are There Gender Differences in Demand for Index-Based Livestock Insurance?. Issue 6 (3rd June 2017) - Bageant, Elizabeth R.; Barrett, Christopher B.
ABSTRACT: Risk management plays a role in avoiding and escaping chronic poverty throughout the world, particularly for women, who are disproportionately negatively affected by shocks. Using three years of household survey data, administrative records and qualitative interviews, this paper examines the relationship between gender and demand for index-based livestock insurance (IBLI) among pastoralists in southern Ethiopia. IBLI appears to be equitably accessed by men and women alike and we find limited evidence of gender-differentiated demand for IBLI. We also find only modest differences associated with age and share of income from livestock.